2019
DOI: 10.1016/j.ijid.2019.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of clinical pathway for upper respiratory tract infections in emergency department

Abstract: Objective: We aimed to demonstrate the benefits of implementing a clinical pathway to decrease the inappropriate use of antibiotics in upper respiratory tract infections (URTI) in an emergency department (ED). Methods: The study was performed in a hospital with 300 beds. All patients who applied with URTI from 1st to 30th of April 2017 were included and the appropriateness of the antibiotics were compared with the patients in the same period in 2016. A checklist for the clinical pathway of URTI was completed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…These results were similar to those of Jenkin et al, who reported an 11.2% relative reduction in antibiotic prescription for non-pneumonia respiratory infection and a 14.4% relative reduction in broad-spectrum antibiotic use during the intervention period [ 12 ]. In addition, Madran et al reported that the rate of antibiotic prescription decreased from 49% pre-implementation of an antibiotic stewardship program (ASP) to 29% post-implementation and that the application of a clinical pathway resulted in a rate of appropriate antibiotic use of 82% [ 13 ]. However, our application of the clinical pathway differed from those in the studies above in that, instead of providing a hard copy, we inserted clinical pathway pop-up windows into the electronic prescription system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results were similar to those of Jenkin et al, who reported an 11.2% relative reduction in antibiotic prescription for non-pneumonia respiratory infection and a 14.4% relative reduction in broad-spectrum antibiotic use during the intervention period [ 12 ]. In addition, Madran et al reported that the rate of antibiotic prescription decreased from 49% pre-implementation of an antibiotic stewardship program (ASP) to 29% post-implementation and that the application of a clinical pathway resulted in a rate of appropriate antibiotic use of 82% [ 13 ]. However, our application of the clinical pathway differed from those in the studies above in that, instead of providing a hard copy, we inserted clinical pathway pop-up windows into the electronic prescription system.…”
Section: Discussionmentioning
confidence: 99%
“…The use of a clinical pathway has been shown to reduce antibiotic use in URI [ 12 , 13 , 14 ]. However, the method of implementation may depend on how medication is dispensed.…”
Section: Introductionmentioning
confidence: 99%
“…The commonly occurring URTI are common cold, tonsillitis, pharyngitis, laryngitis, rhino sinusitis and otitis media. 3 Lower respiratory tract structure includes larynx, vocal folds, trachea, bronchi, bronchioles and alveoli. The most commonly occurring respiratory tract infection are tracheitis, bronchiolitis and pneumonia.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Inappropriate and high rates use of antibiotics can increase antibiotic resistance, healthcare cost, adverse events, and also poor treatment outcomes. [7][8][9] Antibiotic resistance is a growing problem worldwide and now becomes the most serious threat in the field of health. 9,10 Antibiotic consumption is still a concern in Asia-Pacific countries, prescribing at ambulatory care centers reaches 82%.…”
Section: Introductionmentioning
confidence: 99%